2019
DOI: 10.3390/ijms20071757
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate Receptor 5 and 8 Modulate the Ameliorative Effect of Ultramicronized Palmitoylethanolamide on Cognitive Decline Associated with Neuropathic Pain

Abstract: This study investigated whether metabotropic glutamate receptor (mGluR) 5 and 8 are involved in the effect of ultramicronizedpalmitoylethanolamide (um-PEA) on the cognitive behavior and long term potentiation (LTP) at entorhinal cortex (LEC)-dentate gyrus (DG) pathway in mice rendered neuropathic by the spare nerve injury (SNI). SNI reduced discriminative memory and LTP. Um-PEA treatment started after the development of neuropathic pain had no effects in sham mice, whereas it restored cognitive behavior and LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…PEA has no unfavorable effects at pharmacological doses [97]. In addition, several experimental works showed the beneficial effects of new PEA formulations (micronized or ultramicronized) in carrageenan-induced inflammation [98] on cognitive decline associated to neuropathic pain [99] in an Alzheimer disease model [100], tibia fracture mouse model [101], and diabetic neuropathy [102]. Recent observational clinical studies reported the beneficial use of ultramicronized PEA as an add-on therapy in patients suffering from low back pain [103] as well as in patients suffering from fibromyalgia syndrome (FMS) [104].…”
Section: New Therapeutic Strategiesmentioning
confidence: 99%
“…PEA has no unfavorable effects at pharmacological doses [97]. In addition, several experimental works showed the beneficial effects of new PEA formulations (micronized or ultramicronized) in carrageenan-induced inflammation [98] on cognitive decline associated to neuropathic pain [99] in an Alzheimer disease model [100], tibia fracture mouse model [101], and diabetic neuropathy [102]. Recent observational clinical studies reported the beneficial use of ultramicronized PEA as an add-on therapy in patients suffering from low back pain [103] as well as in patients suffering from fibromyalgia syndrome (FMS) [104].…”
Section: New Therapeutic Strategiesmentioning
confidence: 99%
“…There has been reported a link between neuropathic pain (including diabetic neuropathy) and cognitive deficits in rodents (Kodama et al, 2011;Shiers et al, 2018;Boccella et al, 2019;Liang et al, 2020;Won et al, 2020) and humans (Curatolo et al, 2017;Ojeda et al, 2018;Naranjo et al, 2019). However, current therapies for neuropathic pain have not considered this relationship.…”
Section: Cognitive Deficitsmentioning
confidence: 99%
“…Bahi showed that systemic injection of mGlu8 receptor agonist decreases voluntary ethanol intake and ethanol-induced CPP in C57BL/6J mice [ 58 ]. Several studies have suggested that mGlu8 receptors are involved in associative learning [ 59 , 60 ]. Associative learning and synaptic long-term potentiation (LTP) depend on the same cellular mechanisms [ 61 ], which is consistent with our results regarding the inhibitory role of mGlu8 receptors in morphine induced CPP.…”
Section: Discussionmentioning
confidence: 99%